2009
DOI: 10.1111/j.1365-2222.2009.03284.x
|View full text |Cite
|
Sign up to set email alerts
|

The non‐proteolytic house dust mite allergen Der p 2 induce NF‐κB and MAPK dependent activation of bronchial epithelial cells

Abstract: These results show that Der p 2 activates respiratory epithelial cells, indicating that this non-proteolytic allergen, in addition to its immunogenic properties, can aggravate respiratory airway disease by adjuvant-like activation of the lung epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 46 publications
5
77
1
Order By: Relevance
“…36) This trend could be observed in the present study, because the downregulatory effect of SWCNT exposure was not observed in most of the selected genes. Moreover, the different responses observed between A549 cells and FaDu cells might be partly explained by differences in the cell differentiation, because considerable heterogeneity in the expression of heat-shock proteins, one of the best-characterized stress proteins, is observed in different tumor cells from lung carcinoma.…”
Section: Discussionsupporting
confidence: 59%
“…36) This trend could be observed in the present study, because the downregulatory effect of SWCNT exposure was not observed in most of the selected genes. Moreover, the different responses observed between A549 cells and FaDu cells might be partly explained by differences in the cell differentiation, because considerable heterogeneity in the expression of heat-shock proteins, one of the best-characterized stress proteins, is observed in different tumor cells from lung carcinoma.…”
Section: Discussionsupporting
confidence: 59%
“…TLR4 is expressed in many immune and structural cells. Indeed, Der p 2 activates dendritic cells and respiratory EC to produce pro-inflammatory mediators [21,22]. Der p 2 may trigger inflammatory responses by stimulating innate immune response in a TLR4-dependent manner and promote sensitization and development of allergic diseases.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…Their research showed that desensitisation may cause the activation of processes related to PAR-2 receptors (protease-activated receptor) located on the surface of the respiratory epithelial cells. On the other hand, the treatment with Dermatophagoides pteronyssinus resulted in NF-kappaB and mitogen-activated protein kinase (MAPK)-dependent secretion of interleukin, cytokines, and chemokines in bronchial BEAS-2B and human bronchial epithelial cells (NHBE) [21]. In turn, Xiang et al observed the dose-dependent toxic effect of a dust mite on PHCE cell line.…”
Section: F-actinmentioning
confidence: 95%